Sosialization Fintech Literacy Peer to Peer Lending Syariah as Sidoarjo MSME Capital - Fitri Nur Latifah; Novia Ariyanti; Imam Fauji; Nuris Tiswanah (Indonesian Journal of Cultural and Community Development, 2023)
This article explores the transformative role of financial technology (fintech) in Indonesia, specifically focusing on micro, small, and medium enterprises (MSMEs) in Sidoarjo. While fintech presents a promising avenue for MSME growth by providing access to banking services and capital, its adoption is hindered by limited MSME familiarity with fintech tools. In response, this study introduces the Peer-to-Peer Lending Sharia scheme as a viable alternative capital source for nonbankable MSMEs. The research employs a multifaceted approach encompassing awareness campaigns and educational initiatives to boost MSME fintech literacy. Through a comprehensive evaluation, this intervention reveals improved understanding and acceptance of fintech solutions among MSMEs. Consequently, the article underscores the significance of nurturing fintech literacy in enhancing financial inclusion, promoting sustainable MSME expansion, and fostering economic resilience in Indonesia. Highlights: Empowering Nonbankable MSMEs: Explore the impact of fintech adoption, particularly Peer-to-Peer Lending, in enabling growth for traditionally underserved micro, small, and medium enterprises (MSMEs) in Indonesia. Enhancing Fintech Literacy: Investigate the efficacy of literacy initiatives aimed at increasing MSMEs' understanding and utilization of fintech tools, focusing on Peer-to-Peer Lending schemes, to overcome barriers in adoption. Sustainable Economic Resilience: Highlight the potential of improved MSME fintech literacy to foster financial inclusion, promote sustainable business expansion, and contribute to economic resilience within local communities in Sidoarjo, Indonesia. Keywords: Fintech, MSMEs, Peer-to-Peer Lending, Financial Inclusion, Indonesia